2012
DOI: 10.1097/ijg.0b013e31820e2d23
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Changes in Trabeculectomy Blebs After Laser Suture Lysis Using Anterior Segment Coherence Tomography

Abstract: AS-OCT was able to quantify changes in bleb morphology after LSL, some of which were predictive of eventual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…With the use of image processing and objective assessment of areas of vessel invasion, 6 OCTA also may be useful for monitoring vascular changes before and after treatment when assessing new therapies for abnormal corneal neovascularization. 16 Furthermore, the potential clinical applications of anterior segment OCTA may not be limited to the cornea; for example, evaluating conjunctival and scleral vasculature may add further information to bleb morphologic features after glaucoma surgery assessed by OCT. 29 The OCTA system used in this study uses decorrelative techniques to detect phase variations and OCT signal intensity that result from blood flow, which are independent of flow orientation over a larger range of flow velocities. 4 Using the scanning protocol described above, we found that corneal vessels were outlined in the presence of superficial corneal scarring or lipid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of image processing and objective assessment of areas of vessel invasion, 6 OCTA also may be useful for monitoring vascular changes before and after treatment when assessing new therapies for abnormal corneal neovascularization. 16 Furthermore, the potential clinical applications of anterior segment OCTA may not be limited to the cornea; for example, evaluating conjunctival and scleral vasculature may add further information to bleb morphologic features after glaucoma surgery assessed by OCT. 29 The OCTA system used in this study uses decorrelative techniques to detect phase variations and OCT signal intensity that result from blood flow, which are independent of flow orientation over a larger range of flow velocities. 4 Using the scanning protocol described above, we found that corneal vessels were outlined in the presence of superficial corneal scarring or lipid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The potential clinical applications of OCTA for the anterior segment, apart from those already mentioned, could also extend to addition to intra-operative OCT assessment,25 assessment of graft vascularisation with prognostication for graft rejection,26 evaluation of new antiangiogenic treatments for corneal vascularisation,27 studying limbal vasculature associated with limbal stem cell deficiency28 or even evaluation of bleb vascularity and morphology after glaucoma surgery 29. We recognise the limitations of this preliminary study, which describes the adaptation of the retinal OCTA compared with ICGA for the evaluation of corneal vascularisation.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior segment optical coherence tomography (ASOCT) allows a more objective and reproducible assessment of anterior segment structures (Sng et al. , , ; Sng & Barton ). It is a non‐contact optical system, can be performed under standardized dark conditions, and can be operated with minimal expertise by a technician.…”
Section: Introductionmentioning
confidence: 99%